2022
DOI: 10.3847/1538-4357/ac400d
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Multiphase Magnetic Field Tracers in a High Galactic Latitude Region of the Filamentary Interstellar Medium

Abstract: Understanding how the Galactic magnetic field threads the multiphase interstellar medium (ISM) remains a considerable challenge, as different magnetic field tracers probe dissimilar phases and field components. We search for evidence of a common magnetic field shared between the ionized and neutral ISM by comparing 1.4 GHz radio continuum polarization and H i line emission from the Galactic Arecibo L-Band Feed Array Continuum Transit Survey (GALFACTS) and Galactic Arecibo L-Band Feed Array H i (GALFA-H i) surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…However, recent low-frequency radio polarimetric observations of Faraday rotation have generally found a morphological association with cold Hi structures. Campbell et al (2022) used midfrequency radio polarization Faraday rotation to show, for the first time, that the Hi appears clearly connected to the warm ionized medium via a common magnetic field. While they consider whether a compressive event triggered the connection between the Hi and the magnetic field, they cannot definitively conclude that it did.…”
Section: Linking Magnetic Fields To Hi Structurementioning
confidence: 99%
“…However, recent low-frequency radio polarimetric observations of Faraday rotation have generally found a morphological association with cold Hi structures. Campbell et al (2022) used midfrequency radio polarization Faraday rotation to show, for the first time, that the Hi appears clearly connected to the warm ionized medium via a common magnetic field. While they consider whether a compressive event triggered the connection between the Hi and the magnetic field, they cannot definitively conclude that it did.…”
Section: Linking Magnetic Fields To Hi Structurementioning
confidence: 99%
“…The original RHT algorithm outlined above performs well for Galactic sky regions and velocity ranges where the emission is ubiquitous (e.g., Clark et al 2014;Jelić et al 2018;Campbell et al 2022). However, this is far from the case for the SMC in H , for which the presence of emission is highly dependent on the location and the radial velocity (Stanimirovic et al 1999;McClure-Griffiths et al 2018;Di Teodoro et al 2019;Pingel et al 2022).…”
Section: H Filaments From Gaskapmentioning
confidence: 99%
“…High spatial resolution observations have revealed that the H gas in the Milky Way is organised into highly filamentary structures (e.g., McClure-Griffiths et al 2006;Clark et al 2014;Martin et al 2015;Kalberla et al 2016;Blagrave et al 2017;Soler et al 2020;Skalidis et al 2022;Campbell et al 2022;Soler et al 2022;Syed et al 2022). Upon comparisons with starlight and dust polarisation data, it has been found that the elongation of these slender (with presumed widths of 0.1 pc) H filaments is often aligned with their ambient magnetic field orientations (McClure-Griffiths et al 2006;Clark et al 2014Clark et al , 2015Martin et al 2015;Kalberla et al 2016;Clark & Hensley 2019, see Skalidis et al 2022 for a counter-example).…”
Section: Introductionmentioning
confidence: 99%
“…As the resolution and sensitivity of observations improve, we are increasingly finding that the interstellar medium (ISM) of our Galaxy is filled with filamentary (i.e., long and narrow) structures from a variety of different origins. These filaments are observed in emission across the electromagnetic spectrum including with X-rays (e.g., De Vries & Romani 2022), ultraviolet (UV; e.g., Bracco et al 2020), optical (e.g., Fesen et al 2021), infrared (e.g., Green et al 2022), andradio (e.g., Yusef-Zadeh et al 1984;Heywood et al 2022), and there are also long and narrow structures detected through non-emitting tracers such as Faraday rotation (e.g., Campbell et al 2022) and scintillation of background sources (e.g., Wang et al 2021). The filaments are associated with many different environments and origins including star-forming regions, supernova remnants (SNRs), bow shock nebulae, and also filaments of uncertain origins (e.g., Jelić et al 2015;Bracco et al 2020), and the radiation can come from both thermal and nonthermal (i.e., synchrotron) emission mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that the orientation of filaments are connected to magnetic fields (Clark et al 2014;Jelić et al 2015;Zaroubi et al 2015;Planck Collaboration et al 2016;West et al 2021;Campbell et al 2022). Spiral galaxies, including the Milky Way, are known to have coherent large (galactic)-scale magnetic fields (Beck 2015), which are thought to originate through the α − Ω dynamo and compression from spiral shocks and supernova (SN) explosions (Beck 2015).…”
Section: Introductionmentioning
confidence: 99%